2022
DOI: 10.1177/20552076221118828
|View full text |Cite
|
Sign up to set email alerts
|

The effect of information technology intervention on using appropriate VTE prophylaxis in non-surgical patients: A systematic review and meta-analysis

Abstract: Introduction Clinical decision support systems (CDSSs) play an important role in summarizing the best clinical practices, thereby promoting high standards of care in specific medical fields. These systems can serve as tools for gaining knowledge and mediating between clinical guidelines and physicians thereby providing the right information to the right person at the right time. Objective This review aims to evaluate the effect of CDSSs on adherence to guidelines for venous thromboembolism (VTE) prophylaxis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A systematic review of VTE CDS identified a statistically significant increase in appropriate VTE prophylaxis prescribing with use of a CDS system (OR = 1.69, p = .001). 8 We failed to reach statistical significance in terms of increasing VTE prescribing; however, the absolute proportion of patients prescribed pharmacoprophylaxis correctly did increase. The studies in that review included only adult patients.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A systematic review of VTE CDS identified a statistically significant increase in appropriate VTE prophylaxis prescribing with use of a CDS system (OR = 1.69, p = .001). 8 We failed to reach statistical significance in terms of increasing VTE prescribing; however, the absolute proportion of patients prescribed pharmacoprophylaxis correctly did increase. The studies in that review included only adult patients.…”
Section: Discussionmentioning
confidence: 70%
“…Numerous institutions have implemented clinical decision support (CDS) systems to aid providers in stratifying patients VTE risk and in ordering VTE prophylaxis when appropriate 2–7 . A systematic review of 12 studies assessing the utility of CDS systems to improve VTE pharmacologic prophylaxis prescribing found that the use of CDS was associated with a significant increase in guideline‐concordant pharmacologic prophylaxis prescribing and a decrease in the incidence of VTEs 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior groups have designed interventions aimed at improving adherence to VTE prophylaxis guidelines, including real‐time feedback alerts and computerized clinical decision support 13 . Meta‐analyses indicate that electronic health record (EHR) clinical decision support tools lead to increased rates of appropriate VTE prophylaxis prescription and a possible reduction in the incidence of VTE 13,14 . However, the evidence for the impact of interventions in addressing prophylaxis overuse, in particular, is sparse, with only some groups designing tools aimed at both improving underuse and overuse.…”
Section: Introductionmentioning
confidence: 99%
“…13 Meta-analyses indicate that electronic health record (EHR) clinical decision support tools lead to increased rates of appropriate VTE prophylaxis prescription and a possible reduction in the incidence of VTE. 13,14 However, the evidence for the impact of interventions in addressing prophylaxis overuse, in particular, is sparse, with only some groups designing tools aimed at both improving underuse and overuse. When rates of overuse are reported, these interventions have no significant effect.…”
Section: Introductionmentioning
confidence: 99%